Agricultural forestry - Rader, Ralph Waldo (My University, 1895)
Introduction: As we look over the works of nature it is remarkable to notice what a vast amount of its make-up is left to the beauties of vegetation in its various forms. I feel safe in stating that no product of the soil enters so largely into the industries and relative prosperity of the world as its forests. Nearly everything that man works with; his tools, machinery, dwellings and other conveniences, owe their existence to forests; in fact I believe that land, that is not furnished with this element of nature would be of no use to progressive people. Coal mines may be exhausted, oil wells cease to flow, but as long as the earth is populated, our trees will ever be an important factor in its growth. What weary traveler is not glad to enjoy the beautiful shade of a spreading elm tree, after a tiring trip across a hot deserty section, thanking nature for her gift of relief as he comfortably seats himself by a spring of water gushing forth at its base.
Citation: Rader, Ralph Waldo. Agricultural forestry. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Forestry; Horticulture; Trees; Theses; Manuscripts (documents)